2012
DOI: 10.1177/0011128712453677
|View full text |Cite
|
Sign up to set email alerts
|

The Victim-Offender Overlap, Intimate Partner Violence, and Sex

Abstract: This study examines the overlap between victimization and offending within officially recorded incidents of intimate partner violence (IPV). Using official police data, 1,256 individuals are initially differentiated by their role as the victim or the offender in an IPV incident and then categorized into four distinct groups (e.g., as victims, persistent offenders, desistent offenders, or victim-offenders) based on their role in further officially recorded IPV incidents during an 18-to 30-month follow-up period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 62 publications
3
19
1
Order By: Relevance
“…Muftic and colleagues (2015) also found an overlap in IPV using crime report/police data for all adults. From a sample of 1,256 cases of IPV from police reports, 37% were IPV victims only, 17.9% were persistent IPV offenders (individuals who perpetrated IPV in the original incident, but did not experience domestic violence [DV] victimization in the 18+-month follow-up period), 18% were desistent IPV offenders (individuals who engaged in IPV offending in the original incident but had no officially recorded record of IPV incident in the follow-up), and 27.1% were victim-offenders.…”
Section: Ipvmentioning
confidence: 86%
See 2 more Smart Citations
“…Muftic and colleagues (2015) also found an overlap in IPV using crime report/police data for all adults. From a sample of 1,256 cases of IPV from police reports, 37% were IPV victims only, 17.9% were persistent IPV offenders (individuals who perpetrated IPV in the original incident, but did not experience domestic violence [DV] victimization in the 18+-month follow-up period), 18% were desistent IPV offenders (individuals who engaged in IPV offending in the original incident but had no officially recorded record of IPV incident in the follow-up), and 27.1% were victim-offenders.…”
Section: Ipvmentioning
confidence: 86%
“…Our study focuses on assessing the victim–offender overlap among young adults in intimate relationships, an understudied area (Muftić, Finn, & Marsh, 2015; Tillyer & Wright, 2014). Furthermore, a novel approach is used, investigating offending and victimization within and outside of the intimate relationship.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For specific offenses, the categorization of victims only, offenders only, and victimoffenders may vary, but men are in general more involved in committing acts of violence. For instance, it has been demonstrated in regard to intimate partner violence that, although the victim-offender group may be equally large across the sexes, males are much more often offenders without being victims, while women who commit acts of intimate partner violence are much more often also victims of such violence compared with men (Muftić, Finn, & Marsh, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, concerning the victimization of dating violence, several studies have reported that the victims of dating violence are found among groups of youth exhibiting social and health risk behaviours (Nilses, Blom, Heimer, & Danielsson, 2011;Silverman et al, 2001), such as non-violent and violent delinquency, increased levels of substance abuse, and sexual risk behaviours. It has been suggested, in accordance with the theory of gender symmetry (Straus, 2006), that the roles of victim and offender oscillate in violent relationships (Muftić, Finn, & Marsh, 2012).…”
mentioning
confidence: 88%